Optimization of osmotic dehydration of seedless guava (Psidium guajava L.) in sucrose solution using response surface methodology - Ganjloo, Ali; Abdul Rahman, Russly; Bakar, Jamilah; Osman, Azizah; Bimakr, Mandana (Walter de Gruyter, 2014)
In this study, osmotic dehydration of seedless guava was studied through response surface methodology. Seedless guava cubes were dehydrated in sucrose solution at different concentration (30–50% w/w), temperature (30–50°C) and immersion time (15–240 min) with respect to weight reduction, solid gain and water loss. A Box–Behnken design was used to determine the optimum processing conditions that yield maximum weight reduction, water loss and minimum solid gain. The models developed for all responses were significant (p<0.05). The response surface plots were constructed to show the interaction of process variables. Optimum process conditions were found to be sucrose concentration of 33.79% w/w, temperature of 30.00°C and immersion time of 240 min through desirability function method. At these optimum points, weight reduction, solid gain and water loss were found to be 0.189 (gg−1), 0.050 (gg−1) and 0.237 (gg−1), respectively.